Editorial: Challenges of Teaching Languages (Palíndromo, 2024)
This dossier dedicated to the Challenges of Teaching Languages aims to problematize issues related to the complex processes of teaching how to read languages, not just visual languages stricto sensu, but others such as sound, fashion, design, urban planning, mixed languages, such as audiovisual, or illustrated books and even verbal language, in close dialogue or in comparison with visuality. It consists of twelve articles from different areas of knowledge, theoretical approaches and institutions and also celebrates the collaboration between PPGAV, Postgraduate Program in Visual Arts of the State University of Santa Catarina/UDESC and GREPAI, Grup de Recerca in Education, Patrimoni i Arts Intermèdia, from the University of Girona/UdG.
Keywords: aesthetic languages; language teaching; reading of images